Design of a Broadband Inverted Conical Quadrifilar Helix Antenna - Jingyan Mo; Wei Liu; Weidong Fang; Haigao Xue; Zhongchao Lin (International Journal of Antennas and Propagation)
This paper introduces the design of a broadband inverted conical circularly polarized quadrifilar helix antenna (QHA). The antenna has many good characteristics, including wide beam and broad bandwidth, which are achieved by utilizing inverted conical geometry and adjusting the dimensions of the inverted conical support. The antenna is fed by a wideband network to provide 90° phase difference between the four arms with constant amplitude. The antenna impedance and axial ratio bandwidth values are more than 39% and 31.5%, respectively. The measured results coincide well with the simulated ones, which verified the effectiveness of the proposed design.